Pengaruh SIMA, CAR,NPF Terhadap Profitabilitas Dengan FDR Sebagai Variabel Intervening - Muhammad Abdul Manaf; Anton Bawono (Jurnal Akuntansi dan Keuangan Kontemporer (JAKK), 2021)
The purpose of this study was to determine the effect of SIMA, NPF, CAR, on profitability with FDR as the intervening variable. This study uses quantitative research using multiple regression analysis as data analysis. This study uses panel data in the form of Random Effect annual data SIMA, NPF, CAR, FDR, ROA at Islamic commercial banks registered with OJK for the 2016-2019 period. The data obtained in this study were analyzed using the eviews 10 application tool. The results of this study indicate the SIMA variable has a significant positive effect on profitability. Variables NPF, CAR have a negative insignificant effect on profitability then the FDR variable has a positive and insignificant effect on profitability. After conducting path analysis, the FDR variable could not mediate the relationship between SIMA, NPF, CAR variables on profitability.Keywords: SIMA, NPF, CAR, FDR, ROA